Caterpillars in the field and garden - Allen, Thomas J. (Oxford University Press, 2005)
Caterpillars are as varied, fascinating, and often as colorful as the adult butterflies they become. This is the most comprehensive guide to these creatures available. It contains all the information necessary to find and identify the caterpillars of North America--from Two-tailed Swallowtails, some of the largest butterfly caterpillars at just over two inches when fully grown, to tiny Western Pygmy-Blues. Caterpillar seekers will learn how to distinguish between butterfly caterpillars and moth caterpillars, where and how to find caterpillars, and the visual differences between young and older caterpillars